Heritage politics in Adelaide - Mosler, Sharon Ann (University of Adelaide Press, 2011)
"In this study, Sharon Mosler examines heritage issues and conflicts in Adelaide from enactment of the first South Australian Heritage Act in 1978 to its successor in 1993, and also analyses issues leading from that period into the twenty-first century. State legislation introduced by the Labor government of Premier Mike Rann (2002-2011) affected the built environment significantly since this book began. The Rann government gave the built heritage a low priority in its strategic plan compared to population growth, while the Adelaide City Council became more balanced in the past decade, although the council too has focused on increasing Adelaide's population. The result has been more high-rise buildings at the expense of heritage conservation and historic precincts."--Publisher's description